(untitled) (Pakistan Journal of Scientific Research, 2021)
The geographically distributed software development has attained a significant attraction in software development industry since last few decades due to its wide acceptance across the globe. The main essence of geographically distributed software development is to expand company working by follow-the-sun strategy, get skilled labors at cheaper rates from low economy regions of world and pool-up company resources to raise their utilization graph. The requirements elicitation process is considered as one of the most challenging tasks during software development process in traditional as well as geographically distributed software development projects due to its social and collaborative nature. This article presents a comprehensive insight about major challenges faced by requirements elicitation teams engaged in geographically distributed software development projects. The article also elaborates the possible strategies, which can be adopted to minimize the negative impact of geological distribution of software development activities. The presented study will help the requirements elicitation teams to better plane their requirements elicitation sessions for geological distributed software development projects by encountering the expected hurdles.